2020
DOI: 10.3389/fpsyg.2020.01395
|View full text |Cite
|
Sign up to set email alerts
|

Social Desirability in Environmental Psychology Research: Three Meta-Analyses

Abstract: That social desirability might be a confounder of people's survey responses regarding environmental actions has been discussed for a long time. To produce evidence for or against this assumption, we conducted meta-analyses of correlations between social desirability scales and self-reports of environmentally relevant behaviors, intentions, and (broadly defined) attitudes, based on data from 29 previously published papers. The pooled correlations with social desirability are generally small, ranging from 0.06 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 102 publications
3
72
0
2
Order By: Relevance
“…Fifth, despite the efforts to reduce chances of deceitful answers and the effect of social desirability these biases could potentially affect the results of the studies. Although, according to recent study the effect of social desirability bias in pro-environmental behavior studies is rather weak (Vesely and Klöckner, 2020), it is nevertheless important to consider this possible limitation. Future studies could test whether this potential compound affects the relationship between biospheric values, environmental selfidentity, personal norms and pro-environmental behavior in adolescents' studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, despite the efforts to reduce chances of deceitful answers and the effect of social desirability these biases could potentially affect the results of the studies. Although, according to recent study the effect of social desirability bias in pro-environmental behavior studies is rather weak (Vesely and Klöckner, 2020), it is nevertheless important to consider this possible limitation. Future studies could test whether this potential compound affects the relationship between biospheric values, environmental selfidentity, personal norms and pro-environmental behavior in adolescents' studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could test whether this potential compound affects the relationship between biospheric values, environmental selfidentity, personal norms and pro-environmental behavior in adolescents' studies. This is possible through controlling tested models/relationships for general social desirability as well as testing to what extent social norms moderate the relationships between social desirability and variables in question (Vesely and Klöckner, 2020). Sixth, in this study we targeted environmental sustainability in particular, but it is also important to study which factors motivate people to engage in other types of sustainable actions (e.g., reducing inequalities) on an individual as well as organizational and institutional level (e.g., sustainable businesses and industry).…”
Section: Discussionmentioning
confidence: 99%
“…There are no data from this study to support this and it is a different conclusion to that reached by Lee et al (2015) who concluded that, when the subject matter was gambling and its co-morbidities (alcohol, drug and tobacco use), online responses were less susceptible to social desirability because the online survey ensured greater anonymity. Further, Vesely and Klöckner (2020) found little evidence for social desirability to be a confounder of people's survey responses regarding environmental actions, and, to the extent that animal welfare attitudes might align with attitudes toward environmental action, this might apply to the results reported here. However, this is a speculative argument and requires empirical investigation to determine its relevance or validity.…”
Section: Discussionmentioning
confidence: 52%
“…Item scores are summed to produce totals ranging between 0 and 33, with higher scores representing more socially desirable responding. This scale is commonly used to measure and control for response bias in studies involving self-report methods (Larson, 2019;van de Mortel, 2008;Vesely & Klöckner, 2020). The scale showed strong reliability in the current study (Cronbach's α = .80).…”
Section: Methodsmentioning
confidence: 55%